Five Fungal Pathogens Are Responsible for Bayberry Twig Blight and Fungicides Were Screened for Disease Control - Wenjun Li; Ming Hu; Yang Xue; Zhijun Li; Yanfei Zhang; Daoxu Zheng; Guangtao Lu; Junxia Wang; Jianuan Zhou (Microorganisms, 2020)
Bayberry (Myrica rubra) is a commercial fruit in China. For the past seven years, twig blight disease has been attacking bayberry plantations in Shantou City, Guangdong Province, China, leading to destructive damage and financial loss. In this study, five fungal species associated with twig dieback and stem blight were identified based on morphological characteristics combined with multilocus sequence analysis (MLSA) on the internal transcribed spacer (ITS) region, partial sequences of β-tubulin (tub2), translation elongation factor 1-α (tef1-α), large subunit ribosomal RNA (LSU) and small subunit ribosomal RNA (SSU) genes, which are Epicoccum sorghinum, Neofusicoccum parvum, Lasiodiplodia theobromae, Nigrospora oryzae and a Pestalotiopsis new species P. myricae. P. myricae is the chief pathogen in fields, based on its high isolation rate and fast disease progression after inoculation. To our knowledge, this is the first study reporting the above five fungi as the pathogens responsible for bayberry twig blight. Indoor screening of fungicides indicates that Prochloraz (copper salt) is the most promising fungicide for field application, followed by Pyraclostrobin, 15% Difenoconazole + 15% Propiconazole, Difenoconazole and Myclobutanil. Additionally, Bacillus velezensis strain 3–10 and zeamines from Dickeya zeae strain EC1 could be used as potential ecofriendly alternatives to control the disease.